Supervisi Berbasis Nilai-Nilai Al-Qur’an Dalam Menghadapi Tantangan Era Society 5.0 - Budi Winarno; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the model of supervision based on Qur’anic values as a strategic approach to addressing the challenges faced by Islamic education in the Society 5.0 era. The global transformation marked by rapid digitalization requires Islamic educational institutions not only to adapt technologically but also to uphold the integrity of spiritual and moral values. This research employs a qualitative-descriptive approach through literature review combined with field studies at Samingun Barakatul Ummah Foundation (Shaum), Wonogiri. The findings indicate that educational supervision grounded in Qur’anic values effectively bridges the need for technological mastery with the strengthening of moral character. Supervision at Shaum Foundation serves not only administrative oversight but also instills Qur’anic principles such as justice (al-‘adl), trustworthiness (amanah), honesty (ash-shidq), compassion (ar-rahmah), patience (ash-shabr), and knowledge (al-‘ilm). The implementation of Qur’anic-based supervision is reflected in the development of an integrative curriculum, digital literacy training infused with Islamic values, the reinforcement of collective leadership, and institutional governance that integrates technology with sharia-based values. This study concludes that Qur’anic-based supervision effectively enhances teachers’ professionalism, students’ character formation, and adaptive educational management capable of embracing technological advancement without compromising Islamic identity. These findings are expected to provide strategic recommendations for the development of relevant and competitive Islamic educational supervision in the Society 5.0 era.